THE ASSOCIATION BETWEEN TYPE 2 DIABETES MELLITUS AND CARDIOVASCULAR DISEASES: A SYSTEMATIC REVIEW - Frida Setiawan, Yenny (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Aim: The objective of this study is to evaluate the complication of dorsal plication and ventral lengthening technique for penile curvature.Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, ProQuest) and included articles published between 2001–2022. Duplicate publications, review articles, and incomplete articles were excluded.Results: Databases searching identified a total of 254 articles. Of these, 29 articles passed the screening process and resulted in 12 articles for full-text assessment. The 6 articles did not evaluate the outcome of interest. Hence, we found six appropriate studies included in this review.Conclusion: There exists an association between T2DM and CVD. As the incidence of DM continues to rise, it is also possible that the incidence of CVD will increase as a result of both the conventional risk factors for DM and the direct effect of DM on CVD. DM and CVD are on the rise, and their prevalence and progression must be slowed by DM and CVD treatment and control. To improve medical treatment and cardiovascular outcomes for patients with diabetes, additional research is essential to increase understanding of the disease state and its impact on CV function.